COVID-19 symptom duration predicts immunoglobulin G seropositivity - Štěpánek, Ladislav; Nakládalová, Marie; Štěpánek, Lubomír; Janošíková, Magdaléna; Boriková, Alena; Vildová, Helena (Bratislavské lekárske listy, 2021)
OBJECTIVES: The study focused on the relationship between routine clinical characteristics and anti-SARS-CoV-2 specific antibodies in a pilot sample of healthcare workers (HCWs) having suffered COVID-19. The aim was to investigate the existence of readily available predictors of antibodies against COVID-19. METHODS: As part of the recognition of COVID-19 as an occupational disease in 152 HCWs with the mean age of 43.2 years, personal, anthropometric and anamnestic data related to the disease as well as anti-spike immunoglobulin (Ig) levels were obtained. Through descriptive statistics, correlation and regression analyses, relationships of all variables and Ig levels, especially seropositivity of IgG, were investigated. RESULTS: The mean interval between the symptom onset and the determination of antibodies was 58 days. IgG seropositivity and IgM seropositivity were noted in 82 % and 49 % of HCWs, respectively. Symptom duration was the only statistically significant predictor of IgG seropositivity. With each day of symptom duration, the probability of IgG seropositivity increased from 1.078 to 1.092 times (p < 0.05). If symptoms lasted longer than 17 days, a majority (almost 80 %) of the subjects demonstrated seropositivity in the following months. CONCLUSION: The presence of IgG immunity may be assumed from symptom duration. Such easy recognizing of seropositive patients may be a useful tool, e.g. in vaccination strategies (Tab. 3, Fig. 1, Ref. 28).
Keywords: dospělí; COVID-19; Immunoglobulin G; Cross-Sectional Studies; zdravotnický personál; trvání nemoci; nemoci z povolání; Humans; lidé středního věku; Middle Aged; logistické modely; regresní analýza; Kaplanův-Meierův odhad; Czech Republic; séropozitivita; Logistic Models; mužské pohlaví; Česká republika; Adult; průřezové studie; Health Personnel; Statistics as Topic; imunoglobulin G; Regression Analysis; ženské pohlaví; statistika jako téma; lidé; Occupational Diseases; Male; Kaplan-Meier Estimate; Female